195k views
3 votes
What is the inverse of the statement below?
x=y

What is the inverse of the statement below? x=y-example-1

2 Answers

3 votes

Answer:

~x->~y

Explanation:

Inverse of a conditional p->q is not p->not q

So inverse of x->y is ~x->~y

User Bopha
by
4.8k points
1 vote

Answer:

The correct option is A.

Explanation:

The given statement is


x\Rightarrow y

We need to find the inverse of the given statement.

If a and b are two statements, then

Direct statement :
a\Rightarrow b

It means if a is true then b is true.

Inverse statement :
\sim a\Rightarrow \sim b

It means if a is false then b is false is true.

The inverse of given statement is


\sim x\Rightarrow \sim y

Therefore the correct option is A.

User Vineet Singh
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.